AB0635 Measurement of Serum Alpha-Klotho in Systemic Sclerosis Patients: Results from A Pivotal Study. (15th July 2016) - Talotta, R.; Atzeni, F.; Bongiovanni, S.; Ditto, M.C.; Letizia, T.; Vago, T.; Varisco, V.; Rigamonti, F.; Batticciotto, A.; Antivalle, M.; Sarzi Puttini, P.
Abstract : Background: Systemic sclerosis (SSc) is a connective tissue disease characterized by microangiopathy and fibrosis involving skin and inner organs. Furthermore, an aberrant activation of the immune system may contribute, at least in part, to the pathogenesis of the disease. Klotho, expressed both as transmembrane and soluble protein, contributes to prevent ageing, hyperphosphatemia, fibrosis, arteriosclerosis, inflammation, and cancer development. Mice lacking klotho gene expression develop an accelerated ageing, with different phenotypes ranging from atherosclerosis and hyperphosphatemia to skin atrophy and emphysema. A deficiency in klotho expression could be responsible for microangiopathy, calcinosis and fibrosis, which represent common characteristics of systemic sclerosis (fig. 1 ). Objectives: To evaluate the serum concentration of a-klotho in a group of SSc patients compared to healthy controls and to correlate its levels with the degree and the kind of organs involvement, assessed through Mesdger's scale score. Methods: We enrolled 69 patients affected by SSc, according to ACR/EULAR 2013 criteria, and 77 matched HC. Blood samples obtained from both patients and controls were collected and analysed by an ELISA test for the determination of human soluble a-klotho by using an anti-human Klotho Mouse IgG (My Biosource, CA, USA). Scleroderma patients were assessed for disease activity through Mesdger's scale. Moreover, modified Rodnan Skin Score (mRSS), pulmonary function tests, 2D echocardiography, chest high resolution computerized tomography, serum creatinine level, ESR, and CRP were also assessed. Subjects suffering from uncontrolled diabetes, lung obstructive diseases or renal impairment not depending on systemic sclerosis were excluded. Results: Our cohort consisted of 69 SSc patients (61 females, mean age 64.5±12.5 years, mean disease duration 9.1±6.7 years) and 77 healthy controls (28 females, mean age 49, 7±10, 2 years). Demographic data are reported in tab.1. Patients were treated with calcium channels blockers (21 cases), i.v.prostanoids (all), immunosuppressive drugs (prednisone in 22 cases; hydroxychloroquine in 14 cases; mofetilmycophenolate in 3 cases; methotrexate in 6 cases; cyclosporin A in 1 case; azathyoprine in 5 cases). Overall, SSc patients have lower serum klotho concentration than healthy controls (0.45 + 0.43 ng/ml vs 0.59 + 0.39 ng/ml; p=0.023197; fig.2 ). However, in SSc patients Spearman test did not reveal a significant association between the serum concentration of klotho and Mesdger's scores. Furthermore, we did not find any association among klotho levels and mRSS, DLCO/AV, serum creatinine, disease duration, age of the patients, ESR and CRP. Conclusions: To our knowledge, this is the first study aiming to investigate the serum concentration of klotho in SSc patients. Our data showed a lower concentration of klotho in the serum of SSc patients compared to healthy controls. However, klotho levels were not related to the severity of the disease, assessed through Mesdger scale, neither to lung or kidney functional impairment, skin fibrosis or systemic inflammation. Disclosure of Interest: None declared